Global, regional, and national burden of soft tissue and other extraosseous sarcomas, 1990–2021: A Systematic analysis for the global burden of disease study 2021 - Xingyue Yuan; Jianhong He; Ruibo Li (PLoS ONE, 2026)
Background Soft tissue and other extraosseous sarcomas (STOES) are rare malignancies originating from mesenchymal tissues, posing a substantial health burden due to their aggressiveness and complex treatment. Understanding the global, regional, and national burden of STOES is crucial for effective prevention, screening, treatment, and resource allocation. Methods Using the standardized Global Burden of Disease (GBD) methodology, we calculated STOES incidence, prevalence, mortality, and disability-adjusted life years (DALYs) to derive the burden of disease caused by STOES. Results were presented in numerical counts and age-standardized rates per 100,000 population, with an uncertainty interval (UI) to highlight potential statistical variability. The Joinpoint regression analysis was used to analyze the time trend from 1990 to 2021. The method facilitates the calculation of annual percentage change (APC) and average annual percentage change (AAPC) and their corresponding 95% confidence intervals (CI). Results In 2021, the global burden of STOES remained substantial with 96,201 incident cases (ASIR: 1.16 per 100,000), 480,473 prevalent cases, 50,203 deaths (ASMR: 0.6 per 100,000), and 1,677,891 DALYs. Males had higher incidence, prevalence, mortality, and DALY rates than females. Regional disparities were evident, with high-income regions exhibiting higher incidence and prevalence but lower mortality rates compared to low-income regions. Notably, East Asia and Oceania had the lowest incidence rates, while Eastern Sub-Saharan Africa had the highest mortality and DALY rates. A mild downward trend was observed in incidence and prevalence, with more pronounced declines in mortality and DALY rates. Conclusion Despite declining trends, the global burden of STOES remains significant, with notable regional differences. Tailored prevention, early detection, and treatment strategies, along with targeted resource allocation, are crucial. Further research is needed to understand the underlying factors driving these trends and develop effective interventions.